2011
DOI: 10.3389/fgene.2011.00023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal and Post-Weaning Folate Supply on Gene-Specific DNA Methylation in the Small Intestine of Weaning and Adult Apc+/Min and Wild Type Mice

Abstract: Increasing evidence supports the developmental origins of adult health and disease hypothesis which argues for a causal relationship between adverse early life nutrition and increased disease risk in adulthood. Modulation of epigenetic marks, e.g., DNA methylation and consequential altered gene expression, has been proposed as a mechanism mediating these effects. Via its role as a methyl donor, dietary folate supply may influence DNA methylation. As aberrant methylation is an early event in colorectal cancer (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The data revealed distinct alterations in DNA methylation at these loci, in both wild-type and Apc +/Min rats, at the stages of weaning and during adulthood (McKay et al, 2011b). The results of this experiment showed that the same folate exposure alters DNA methylation in a gene-and tissue-specific manner at different life stages.…”
Section: 21)mentioning
confidence: 69%
“…The data revealed distinct alterations in DNA methylation at these loci, in both wild-type and Apc +/Min rats, at the stages of weaning and during adulthood (McKay et al, 2011b). The results of this experiment showed that the same folate exposure alters DNA methylation in a gene-and tissue-specific manner at different life stages.…”
Section: 21)mentioning
confidence: 69%
“…A maternal diet deplete of folic acid fed to Apc +/ Min and wild-type mice had no effect on gene-specifi c DNA methylation in weaning mice from both groups. However, decreased genespecifi c DNA methylation at p53 in the small intestine of adult mice was seen with the depleted maternal folic acid diet (McKay et al 2011b ). Furthermore, a low folic acid diet in the postweaning period increased DNA methylation at the Apc gene in the Apc +/ Min mice but not in the wild-type mice (McKay et al 2011b ).…”
Section: Trans-generational Studiesmentioning
confidence: 99%
“…However, decreased genespecifi c DNA methylation at p53 in the small intestine of adult mice was seen with the depleted maternal folic acid diet (McKay et al 2011b ). Furthermore, a low folic acid diet in the postweaning period increased DNA methylation at the Apc gene in the Apc +/ Min mice but not in the wild-type mice (McKay et al 2011b ). Sie et al have recently reported signifi cant decreases in DNA methylation of the promoter regions of the Pparγ and ERα genes and in specifi c exons of the p53 and Apc genes in the liver of offspring at weaning due to maternal folic acid supplementation (Sie et al 2013 ).…”
Section: Trans-generational Studiesmentioning
confidence: 99%
“…A summary of the 13 studies [39,[57][58][59][60][61][62][63][64][65][66][67][68] is presented in Table 1, with highlights of the significant outcomes from each. Fig.…”
Section: Studies Meeting the Inclusion Criteriamentioning
confidence: 99%
“…Recently, McKay et al [68] published their investigation on effects of maternal folate deficiency on DNA methylation in the offspring. Female C57Bl6/J mice were given either a folate replete (2 mg folic acid/kg diet) or low folate (0.4 mg folic acid/kg diet) diet, from mating with Apc Min/+ males, throughout pregnancy and lactation.…”
Section: Studies Which Investigated Folate Deficiency Onlymentioning
confidence: 99%